KAJIAN KONSEP MUSIC ARCHITECTURE PADA JEWISH MUSEUM - Vivaldi Rizqi Hisyam; Ari Widyati Purwantiasning (Ide dan Dialog Desain Indonesia (Idealog), 2022)
In this study, the writer will discuss about the application of the music architecture concept to the performance building. One of the things that is the reason for the importance of this study is discussed because the condition of the music in Indonesia has been growing rapidly but the lack of performance buildings as a venue for music concerts for musicians. Meanwhile, the problem of this research is the implementation of performance building design related to music and architecture. The purpose of this research itself is the relationship and application of music architecture to the performance building according to the case study, namely the Jewish Museum building. This research method uses descriptive qualitative, by analyzing the concept of music architecture in the Jewish Museum building.